2016
DOI: 10.1007/s11102-016-0738-x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in cost of care for pituitary tumor surgery

Abstract: Within New York State, significant geographic variation exists in the cost for transsphenoidal pituitary surgery. The significance of and contributors to such variation is an important question for patients, providers, and policy makers. Transparency of hospital charges, costs, and average length of stay for procedures to the public provides useful information for informed decision-making, especially for a highly portable disease entity like pituitary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…5,7,8 Lee et al showed that there is significant variation in charges and costs for transsphenoidal surgery within New York. 9 While they studied hospital costs and charges and cost-to-charge ratios, they did not evaluate patient and hospital characteristics and their relation to hospital charge. By studying these factors, we can better understand variations in health care costs and thereby, instrument approaches to reduce disparities in hospital charge.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8 Lee et al showed that there is significant variation in charges and costs for transsphenoidal surgery within New York. 9 While they studied hospital costs and charges and cost-to-charge ratios, they did not evaluate patient and hospital characteristics and their relation to hospital charge. By studying these factors, we can better understand variations in health care costs and thereby, instrument approaches to reduce disparities in hospital charge.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 Endoscopic transphenoidal pituitary surgery is a commonly performed skull base operation and is associated with significant cost variability among patients, hospitals, and regions. [12][13][14] While prior work has examined costeffectiveness of various approaches to management of pituitary adenomas, [14][15][16][17][18][19][20][21][22][23][24] less is known regarding the patient and clinical factors that drive in-patient hospital costs following endoscopic transphenoidal pituitary surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare spending in the United States in general, and for TSS specifically, varies widely by geography. 5,6,13,20,23 It is not always the case, however, that higher costs in different geographic regions correspond to better health outcomes. 26 Understanding and reconciling regional differences in practice and referral patterns is thus an important step in reducing wasteful charges for TSS.…”
Section: Geographymentioning
confidence: 99%
“…Some have also advocated for greater transparency of hospital charges, which can help patients make more informed decisions about where they want to receive care, which may in turn introduce a level of competition that incentivizes charge reduction. 20…”
Section: Geographymentioning
confidence: 99%